Design principles in DDR: a case of developing a learning support tool for Malaysian online learners - Alias, Nor Aziah; Sahrir, Muhammad Sabri (MASHI Publication Sdn Bhd, 2012)
Design and Development Research (DDR) focuses on designing and exploring the whole range of designed innovations: products, artefacts and models as well as less concrete aspects such as programmes, activity and curricula. Many researchers have designed, developed, and evaluated products in the field of instructional technology. Yet there is a scarcity of research literature that illustrates how a design is conceptualised or how the design principles are drawn to guide the design and the development of the Learning Support Tool for Malaysian Online Learners.